Global norms and local courts : translating 'the rule of law' in Bangladesh - Berger, Tobias (India : Oxford University Press, 2017)
This book examines the interaction between global norms and local contexts, from global norms about 'the rule of law' from the desks of development experts in Brussels to villages in rural Bangladesh, and what happens to 'the rule of law'.
Includes bibliographical references and index.
Keywords: Rule of law; Rule of law -- Bangladesh